Daily Life Encounters Between the Byzantines and the Ottomans - ÇELİK, SİREN (My University, 2024)
The Byzantines and the Ottomans were both rivals and neighbours. They were also in close cultural contact: they observed each other’s customs, clothing and food. Byzantine literary texts from this period, such as histories and dialogues on Christianity and Islam, are invaluable sources in this sphere, offering insight not only into these respective religions but also providing many instances of cultural encounters. This paper presents some vignettes of daily life encounters between the Byzantines and the Ottomans, especially exploring the Byzantines’ perception of the Ottomans’ customs and food. We will analyse selected passages from the history of John VI Kantakouzenos and the dialogues of Gregory Palamas and Manuel II Palaiologos from this perspective. We will discuss the authors’ perception and representation of the Ottomans as the “other” through depictions of food, customs and daily life routines. Furthermore, these accounts will be supplemented with some key travellers’ accounts, such as those of Ruy Gonzalez de Clavjio and Bertrandon de la Broqiuère. The representations of the Ottomans in these travellers’ accounts will be compared with those of the Byzantine authors. At the same time, the insights they offer into the lives of the Byzantines and the Ottomans will also be investigated. Keywords: Byzantine-Ottoman relations, religious dialogue, cultural history, history of food, late medieval Anatolia.

Bizanslılar ve Osmanlılar hem rakip hem de komşuydular. İki toplum, birbirleriyle yakın kültürel temas içindeydiler ve birbirlerinin adetlerini, giysi ve yemeklerini gözlemliyorlardı. Tarih eserleri, Hristiyanlık ve İslam hakkında yazılmış Bizans diyalogları gibi Geç Bizans metinleri bu konular için son derece zengin kaynaklardır; sadece bu iki dinin algılanışına ışık tutmaz, ayrıca pek çok kültürel karşılaşma anlatısı bulundururlar. Bu makale, Bizanslılar ve Osmanlılar arasındaki bazı günlük hayat karşılaşmalarını ele almayı, özellikle Bizanslı yazarların Osmanlıların adetleri ve yemekleri hakkındaki görüşlerini tartışmayı amaçlamaktadır. Makalede, VI. Ioannes Kantakouzenos’un tarih eserinden ve Gregorios Palamas ile II. Manuel Palaiologos’un diyaloglarından pasajlar incelenecektir. Yazarların Osmanlılara olan bakışı ve onları yemekler, adetler ve günlük hayat rutinleri üzerinden ‘öteki’ olarak tasvir etmeleri tartışılacaktır. Ayrıca, bu anlatılar Ruy Gonzalez de Clavjio ve Bertrandon de la Broqiuère gibi dönemin bazı seyahatnameleriyle desteklenecektir. Bu seyahatnamelerdeki Osmanlı tasvirleri Bizans yazarlarının tasvirleriyle kıyaslanacak, seyyahların Bizanslıların ve Osmanlıların hayatlarına dair anlatıları incelenecektir. Anahtar Kelimeler: Bizans-Osmanlı ilişkileri, dinî diyalog, kültürel tarih, yemek tarihi, Geç Orta Çağ Anadolusu.
Bizanslılar ve Osmanlılar Arasında Kültürel Karşılaşmalar
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Social Sciences and Humanities; History; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; TARİH; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; HISTORY; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Bizans-Osmanlı ilişkileri; dinî diyalog; kültürel tarih; yemek tarihi; Geç Orta Çağ Anadolusu; Byzantine-Ottoman relations; religious dialogue; cultural history; history of food; late medieval Anatolia